The horrors and absurdities of religion - Schopenhauer,Arthur (London Penguin, 2009)
A fascinating examination of ethics, religion and psychology, this selection of Schopenhauer's works contains scathing attack on the nature and logic of religion, and an essay on ethics that ranges from the American slavery debate to the vices of Buddhism. Throughout history, some books have changed the world. They have transformed the way we see ourselves - and each other. They have inspired debate, dissent, war and revolution. They have enlightened, outraged, provoked and comforted. They have enriched lives - and destroyed them. Now Penguin brings you the works of the great thinkers, pioneers, radicals and visionaries whose ideas shook civilization and helped make us who we are.
Keywords: Religion